A Sustainable Environment for whom? - Carneiro, Fernando Ferreira; Pessoa, Vanira Matos (Rev Rene, 2016)
The recognition of the importance of the environmental issue in the social determination of health is related to the evolution of the paradigms concerning health since the times of the treaty “Of the airs, waters and places”, produced by Hippocrates, going through the studies on the precariousness of the life situation of the working class in the period of the Industrial Revolution, up to the complex web of contexts and risks associated with the globalized development model in contemporaneity.